2014
DOI: 10.1007/978-3-319-10265-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Mining Medical Data to Obtain Fuzzy Predicates

Abstract: The collection of methods known as "data mining" offers methodological and technical solutions to deal with the analysis of medical data and the construction of models. Medical data have a special status based upon their applicability to all people; their urgency (including life-or death); and a moral obligation to be used for beneficial purposes. Due to this reality, this article addresses the special features of data mining with medical data. Specifically, we will apply a recent data mining algorithm called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…by the proposed algorithm are novel and the experiments showed that the traditional ARM techniques were unable to discover these rules. Predicate logic in combination with fuzzy logic has been studied by Ceruto et al (2014) and proposed an algorithm called FuzzyPred and implemented on multiple medical datasets. The proposed algorithm obtains patterns through fuzzy predicates representing the dependence between items in the datasets.…”
Section: Predicate Logic and Inference Rulesmentioning
confidence: 99%
“…by the proposed algorithm are novel and the experiments showed that the traditional ARM techniques were unable to discover these rules. Predicate logic in combination with fuzzy logic has been studied by Ceruto et al (2014) and proposed an algorithm called FuzzyPred and implemented on multiple medical datasets. The proposed algorithm obtains patterns through fuzzy predicates representing the dependence between items in the datasets.…”
Section: Predicate Logic and Inference Rulesmentioning
confidence: 99%
“…Sharma et al [7] have discussed potential future instances for casual association examination research as well as data mining approaches and the subject of relational connection assessment. For the most advantageous aspects of employing clinical data for data mining, Ceruto et al [8] have kept a close eye. We will use the Fluffy red information mining calculation in particular.…”
Section: Introductionmentioning
confidence: 99%